SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN DOSEN TETAP DI UNIVERSITAS LABUHAN BATU MENGGUNAKAN METODE SAW - Esterlin Telaumbanua; Volvo Sihombing; Deci Irmayani (Politeknik Bisnis Indonesia, 2021)
Decision Support System (DSS) is generally defined as a system capable of providing both problem-solving capabilities and communications capabilities for semi-structured problems. Lecturers are lecturers in higher education institutions, and lecturers are in charge of implementing the tridharma of higher education, which includes education and teaching, research and development of science and technology and community service and supporting activities. And lecturers are teachers who will produce human resources (Human Resources) so that required systems that can be able to produce the best and professional decisions. Simple Additive Weighting ( SAW ) method requires the process of normalizing the decision matrix (X) to a scale comparable to all existing alternative ratings and has 5 criteria such as: graduate, landfill test, microteaching, interview, TPA and of several criteria have several sets. From the determination of criteria and the set can result in the rank and final results of the election of the right lecturer.The results obtained from the test is the decision of the lecturer who get the best value in accordance with predetermined criteria.